A Meta Analysis Study of the Student Teams Achievement Divisions (STAD) Method in English Teaching and Learning - Hadeli Hadeli; Natasya Sugara; Elismawati Elismawati; Hidayat Al Azmi (AT-TA'LIM, 2022)
This study aims to analyze the effectiveness of the STAD method towards English teaching and learning. The method use in this research is meta-analysis. Data collection is carry out using coding data sheets in which researcher code information from research articles in journals about the use of the STAD method in English teaching and learning. The data are analyze by calculating the effect size. The results of the study reveal that overall the STAD method is effective in influencing English learning as much as 1.53 or is in the category of large effect. The STAD method also has an impressive impact in terms of areas with a magnitude of 1.31 in Indonesia. In addition, based on education level, the result of the large effect is 0.9 at the junior high school level and 1.9 at the high school level. On the other hand, the effect on students' English proficiency is 1.64. STAD affects reading, speaking, and writing skills in English with a large effect value of 1.05, 0.81, and 3.07. From these results, it can be concluded that the STAD method is effective to be applied in learning English because STAD has a great influence in various regions in Indonesia, in education levels, and can improve students' English skills in various aspects.